Effect of Modi"ied Atmospheric Packaging on Extending Shelf LifeofCurryLeaves (MurrayakoenigiiL.) - Kumara, B.A.M.S.; Ekanayake, L.S.K.; Weerasinghe, W.M.S.S.K.; Wijewardane, R.M.N.A.; Sarananda, K.H. (University of Jaffna, 2020)
Curry leaves tree (Murraya koenigii L.) is a popular leafy spice and a leafy vegetable used in Sri Lanka and many other countries, except its usage for medicinal purposes due to phytochemicals present in the plant. Even though it is a very useful and commonly used herb, the freshness and the post-harvest shelf life under ambient condition is around for two days which is a huge limitation for marketing. Modified atmospheric packaging (MAP) has used as an effectivemethod to extend the shelf life of fresh commodities including leafy vegetables. Hence, this experiment was planned to evaluate the effectiveness of MAP on post-harvest shelf life of Curry leaves. Experimental treatments were perforated and non-perforated low density polyethylene bags with gauge 150 (38 micron) and 300 (75 micron) where control samples without package. Thirty gram bundles of fresh curry leaves were used per each treatment. Leaf color values (L*, a* and b*), leaf defoliation percentage, physiological weight loss, chlorophyll content, total carotene content and visual observations were used as measurements. Control samples existed only for 2 days where completely dried out at 3 day of storage. Irrespective of the thickness, perforated rd polyethylene packages extended the shelf life for 4 days. Sealed polyethylene of thickness 75 micron showed one day of storage life where it produce unpleasant odor at 2 day of storage. Sealed polyethylene thickness of 38 micron extended the shelf nd life up to 6 days which was 200% increment of storage period.At6%defoliation level, samples were considered as unmarketable and end of storage life.
Keywords: Leaf color.; Leafy vegetable.; MA packaging; Post-harvest.; Spice